2016
DOI: 10.1080/14330237.2016.1208928
|View full text |Cite
|
Sign up to set email alerts
|

Workplace ethics culture and work engagement: The mediating effect of ethical leadership in a developing world context

Abstract: This study examined the mediating effect of ethical leadership on the relationship between workplace ethics culture and work engagement among employees in a railway transport organisation in the Democratic Republic of the Congo (DRC). The sample consisted of (n = 839: females = 32%) permanently employed staff in a railway organisation in the DRC. The employees were required to complete the Ethical Leadership Scale (ELS), the Ethical Corporate Virtue model (ECV) and the Utrecht Work Engagement Scale (UWES). Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
(30 reference statements)
3
19
0
Order By: Relevance
“…This finding is consistent with Tanner et al (2010), who also found a moderate positive correlation between the perceived ethical leadership behavior and work engagement (r = 0.34). In this sense, when the worker perceives that he receives support from his leader and is treated fairly and respectfully, he usually becomes more involved in his tasks and, consequently, manifests more feelings of vigor, dedication and absorption in those activities Mitonga-Monga et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with Tanner et al (2010), who also found a moderate positive correlation between the perceived ethical leadership behavior and work engagement (r = 0.34). In this sense, when the worker perceives that he receives support from his leader and is treated fairly and respectfully, he usually becomes more involved in his tasks and, consequently, manifests more feelings of vigor, dedication and absorption in those activities Mitonga-Monga et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the perception of ethical leadership behavior can favor greater work engagement when workers observe their leader acting ethically with them. In other words, when employees are treated with respect and justice (Tanner et al, 2010), they tend to manifest positive mental states and engage further in fulfilling their tasks and achieving their work goals (Demirtas, Hannah, Gok, Arslan, & Capar, 2015;Mitonga-Monga, Flotman, & Cilliers, 2016). In this sense, the hypothesis was raised of a moderate positive correlation between the perception of the direct leader's ethical leadership behavior and the work engagement of the employee (H3).…”
mentioning
confidence: 99%
“…Affective commitment and intention to exit are also part of work engagement [50]. Workplace ethical culture through mediation from perceived ethical leadership has a significantly positive effect on work engagement in the whole dimensions-vigor, dedication, and absorption [51].…”
Section: Impact On Work Engagement and Learning Agilitymentioning
confidence: 99%
“…The DRC is a developing country, with considerable economic potential because of its vast mineral and natural wealth [16]. However, political and economic instability have resulted in high levels of inflation, unemployment, and liquidation of companies, retrenchments, corruption, and the under-development of infrastructure [17].…”
Section: The Democratic Republic Of Congo's Work Contextmentioning
confidence: 99%
“…However, political and economic instability have resulted in high levels of inflation, unemployment, and liquidation of companies, retrenchments, corruption, and the under-development of infrastructure [17]. Security and human rights within workplaces are limited [18], which has resulted in the country ranked below 7% on all six indicators [12], with the lowest scores on government effectiveness, rule of law, political stability, and control of corruption [16]. The country's manufacturing sector lacks basic infrastructure, while employees perceive poor leadership, which impacts production negatively.…”
Section: The Democratic Republic Of Congo's Work Contextmentioning
confidence: 99%